Interaction Between Tire Shreds, Rubber-Sand and Geosynthetics. Issue 6 (1st January 1997) - Lovell, C.W.; Salgado, R.; Swan, R.H.; Bernal, A.
Abstract : Waste tires can be shredded (tire shreds) and re-used as fill material. The fill material may be comprised solely of tire shreds or mixed with sand (rubber-sand). If geosynthetics are to be used with fills containing tire shreds, it is necessary to understand the physical interaction between tire shreds, or rubber-sand, and the geosynthetic of interest. A laboratory testing program consisting of direct shear tests, interface direct shear tests, and geosynthetic pullout tests was conducted to determine the interaction properties of tire shreds and rubber-sand fills with three different flexible geogrids and a woven geotextile. Direct shear and interface direct shear tests were conducted using a large direct shear box with dimensions of 300 mm by 300 mm and a total depth of 230 mm. Pullout tests were carried out in a large pullout box with dimensions of 1.2 m in length by 0.9 m in width and a total depth of 0.5 m. The details of the testing program, the test results, and conclusions based on the test results are presented in this paper.